1985
DOI: 10.3109/00365518509155264
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the fluorescein dilaurate pancreatic function test

Abstract: The indirect pancreatic function test, the fluorescein dilaurate test, was performed twice on nine healthy volunteers. The test is based on the renal excretion of fluorescein liberated from an ingested fluorescein ester by pancreatic enzymes. As a control, fluorescein sodium was ingested under similar conditions. The results of the test are expressed as the ratio of the amount of fluorescein excreted in the test part and the control part, forming the test/control (T/C) ratio. The mean values of excreted fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In a first study, the response to secretin stimulation in terms of hydrokinetic pancreatic function, sphincter of Oddi motor function and extensibility of Wirsung's duct was investigated, and none of the parameters proved to be affected by age [63]. The fluorescein dilaurate test reported no decrease in exocrine pancreatic function measured in individuals aged 66-88 years [64]; however, this test is notoriously inconsistent and therefore no longer available [65,66]. Furthermore, investigation of faecal elastase-1 levels in over 90-year-old subjects revealed that only one of 68 patients had low levels and that there was no correlation between faecal elastase-1 and age [67].…”
Section: Age-related Changes In Pancreatic Functionmentioning
confidence: 99%
“…In a first study, the response to secretin stimulation in terms of hydrokinetic pancreatic function, sphincter of Oddi motor function and extensibility of Wirsung's duct was investigated, and none of the parameters proved to be affected by age [63]. The fluorescein dilaurate test reported no decrease in exocrine pancreatic function measured in individuals aged 66-88 years [64]; however, this test is notoriously inconsistent and therefore no longer available [65,66]. Furthermore, investigation of faecal elastase-1 levels in over 90-year-old subjects revealed that only one of 68 patients had low levels and that there was no correlation between faecal elastase-1 and age [67].…”
Section: Age-related Changes In Pancreatic Functionmentioning
confidence: 99%